Implementasi Esp8266 Deauther Versi 2 Sebagai Media Uji Jaringan Nirkabel Terhadap Serangan Deauthentication Pada Pt. Jaring Solusi Persada Cabang Tulungagung - Diyah Anggraini; Yayak Kartika Sari; Joko Iskandar (LPPM Universitas Bhinneka Nusantara, 2026)
The rapid advancement of wireless network technology and the Internet of Things (IoT) ecosystem in the industrial sector carries significant security risks, particularly regarding vulnerabilities within the management frame protocol. This study aims to evaluate the resilience of wireless network infrastructure against communication disruptions at the protocol level, specifically deauthentication attacks, at PT Jaring Solusi Persada (JSP) Tulungagung Branch. Applying a Research and Development (R&D) method with a Prototyping approach , empirical and real-time testing was conducted using a low-power ESP8266 Deauther Version 2 device as a penetration medium across 15 different access points (APs). Quality of Service (QoS) parameters, including throughput, latency, and packet loss, were measured using Wireshark software to analyze network performance degradation in detail. The experimental results reveal that deauthentication attacks inflict a highly destructive impact on vulnerable devices. Out of the 15 tested APs, 6 units (40%) consisting of consumer-grade devices (such as TP-Link, ZTE, and Totolink) were declared vulnerable because they did not support or activate the Management Frame Protection (MFP/IEEE 802.11w) feature. On these vulnerable devices, the attack successfully triggered complete client disconnections, a drastic 70% drop in throughput (from 567 kbps to 170 kbps), extreme latency spikes ranging from 100 to 300 ms, and a packet loss of 15%. Conversely, 9 AP units (60%), dominated by Ruijie Enterprise business-class devices, successfully withstood the attack and maintained stable network connections due to superior hardware specifications and better defense configurations. This study recommends upgrading network security standards to WPA3 and strictly enabling the Protected Management Frames (PMF) feature to ensure the company's operational continuity.